Persistence of Colistin Resistance and mcr-1.1-Positive E. coli in Poultry Despite Colistin Ban in Japan - Komei Kawano; Takayuki Masaki; Tatsuya Kawaguchi; Makoto Kuroda (Antibiotics)
Colistin, a polymyxin antibiotic used as a last-resort treatment for serious infections, exhibits efficacy against multidrug-resistant organisms. Colistin-resistant bacteria limit the treatment options and increase the risk of untreatable infections. In this study, we investigated various antimicrobial-resistant Escherichia coli strains isolated from broiler cecal feces. In the primary screening using CHROMagar C3GR and ESBL, 147 E. coli isolates were obtained from 231 broiler cecal samples at five domestic poultry farms in Japan in 2024. Of the 147 isolates tested for antimicrobial susceptibility, 20 (13.6%) showed resistance to colistin. Moreover, whole-genome sequencing detected the colistin resistance gene, mcr-1.1 (phosphoethanolamine transferase), in the colistin-resistant E. coli strains isolated from the tested five poultry farms. Multilocus sequence typing revealed that all strains belonged to ST1485, indicating that the cloned strains had spread to multiple poultry farms. Subsequent core-genome comparison analysis with global ST1485 strains indicated that the ST1485 isolates in this study were highly identical, whereas the global strains were distinct. The complete genome sequence of BroCaecum-55 contained mcr-1.1 in a 62,716 bp IncI2 replicon plasmid (pBroCa-55-p2). In conclusion, mcr-1.1-positive colistin-resistant E. coli strains, which are rarely reported in Japan, were isolated from Japanese broilers, indicating that colistin resistance persisted even after the ban on colistin use as a feed additive in Japan in 2018. Our findings highlight the need for continuous monitoring of colistin-resistant bacteria in livestock to reduce the transmission risk to humans.